Construção e validação de instrumento para verificar adesão às Diretrizes Brasileiras de Ventilação Mecânica invasiva - CELESTE, Larissa Fernanda do Nascimento (2018)
Ventilatory support aims to maintain pulmonary ventilation and/ or oxygenation of patients unable to do. The patient requiring mechanical ventilation needs specific care, due to their clinical condition, wich makes him more vulnerable. The Brazilian recommendations of mechanical ventilation were developed to gather in a single document the recommendations based on evidence for mechanical ventilation in adults, with the goal to improve understanding of the subject and optimize patient care. The aim of this study was develop and validate an instrument to measure adherence to The Brazilian recommendations of mechanical ventilation of health professionals involved in the care of patients with invasive mechanical ventilation. This is a methodological research, developed in three stages: evaluation of the instrument (Stage I), called IVA-DBVM-I in this study, apparent and content validation (Stage II) and analysis of measurement properties by the criterion validity and instrument reliability (Stage III). To test the instrument reliability, the internal consistency was determinate using Cronbach’s alpha coefficient and the reproducibility with the interobserver agreement, using the Kappa coefficient (k) to analyses the items and the Intraclass Correlation Coefficient (ICC) to the overall scores analysis. For criterion validity, we used the Pearson’s correlation coefficient (r). The apparent and content validation were relevant and indicates that the items was approved in the evaluation by the judges, the content validity index (CVI) was 0,95. The instrument was applied in 87 patients admitted in the Clinic Hospital of the Federal University of Triangulo Mineiro, using invasive mechanical ventilation between 24 and 48 hours. Of the sample, 56,3% were male, with an average age of 60 years (±19,8), there was a prevalence of diagnoses of cardiovascular causes (28,7%). The Cronbach’s alpha coefficient was 0,69. Analyzing the the instrument reliability with the interobserver agreement in 30 items of the instrument, the concordance ratio varied between 95 and 100%. The most part of the agreement measure was classified as perfect (k=1,0), the ICC value was 0,96 to the overall instrument’s score; 0,98, 0.97 and 0,89 to the domains B - Parameters of InvasiveMechanical Ventilation, C - Care associated with Invasive Mechanical Ventilation and D - Sedation and Analgesia, respectively, all statistically significant (p<0,001). The criterion validity identified a positive correlation and moderate magnitude (r=0,31; p< 0,005) between the instrument overall score and peripheral oxygen saturation in the moment of the evaluation. The results show that the instrument of this study is valid and reliable and can be used in the clinical practice of health professionals and also as a tool for management and research.